Urgent Need of Continuing Medical Education: The Key for Patient Awareness of Labor Epidural Analgesia – A Survey of Chinese Perinatal Care Providers. Issue 3 (25th July 2021) - Zhao, Peishan; Hu, Ling-Qun; Liu, Chunyuan; Li, Huiling; Huang, Anna; Yang, Shuwei; Cai, Zhenyu
Abstract: Objective: This survey was designed to understand the misconceptions about labor epidurals. Methods: This voluntary and anonymous online survey on wenjuan.com was conducted from September 1 st, 2015 to January 1 st, 2016 via mainly WeChat groups dedicated to perinatal healthcare providers in China. The questionnaire included items inquiring the knowledge and opinions about labor epidural analgesia related to maternal complications, baby safety, and effect on laboring. Incomplete surveys were excluded from the data analysis. The data was presented as percentages and a Chi-square test or Fisher's exact test, as appreciate, was used to quantitatively compare the results. Results: A total of 1412 respondents completed surveys with 42.9% (606/1412) of them being anesthesiologists, 35.1% (495/1412) being obstetricians, 11.8% (167/1412) being midwives, 3.7% (52/1412) being labor and delivery nurses, and 6.5% (92/1412) being hospital administrators and unspecified. The study revealed a lack of knowledge in labor pain control. Although 82.4% (1164/1412) of respondents were familiar with labor epidural analgesia, 8.9% (126/1412) did not know how it works, and 1.1% (15/1412) never heard it in a multiple-choice question. The three main groups (anesthesiologists, obstetricians, and midwives/labor and delivery nurses) were chosen for comparisons. Opinions among these three groups concerning five questions in the three main concerns were evaluated using a statistical significance of P  < 0.05. Conclusion: The results in our survey indicated an urgent need of continuing medical education to multidisciplinary specialties to improve evidence-based medical practices as these misconceptions have existed for over 10 years in the medical professionals. Lack of public awareness fueled by misconceptions related to labor epidural analgesia may be associated with a lack of professional knowledge. Correct knowledge in professionals needs to be disseminated to the public in order to dispel possible misconceptions and rumors about labor epidural analgesia. This would not only enhance patient understanding of their care but also improve maternal, fetal, and neonatal outcomes.